2019
DOI: 10.2147/cmar.s196025
|View full text |Cite|
|
Sign up to set email alerts
|

<p>The lncRNA HOXA11-AS regulates Rab3D expression by sponging miR-125a-5p promoting metastasis of osteosarcoma</p>

Abstract: Objective: Many studies have shown that long non-coding RNAs (lncRNAs) are closely related to various cancers. This study aims to explore the roles of lncRNA HOXA11-AS in the development and progression of osteosarcoma (OS). Methods: The expression levels of HOXA11-AS and miR-125a-5p in tumor tissues and the adjacent tissues were detected by RT-PCR method. The proliferation, migration and invasion of MG-63 and KHOS cells were determined. Results: It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The invasion of OS cells showed no difference between the inhibitor miR-1972+ pLKO.1-vector group and the inhibitor miR-1972+ pLKO.1-LINC00588 group (*P < 0.05, **0.01 < p < 0.05). (Cao et al, 2019). Similarly, Xu et al found that lncRNA SNHG4 could promote tumor growth by sponging miR-224-3p (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The invasion of OS cells showed no difference between the inhibitor miR-1972+ pLKO.1-vector group and the inhibitor miR-1972+ pLKO.1-LINC00588 group (*P < 0.05, **0.01 < p < 0.05). (Cao et al, 2019). Similarly, Xu et al found that lncRNA SNHG4 could promote tumor growth by sponging miR-224-3p (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…In gastric cancer, oral squamous cell carcinoma, osteosarcoma, renal cancer, hepatocellular carcinoma, breast cancer, prostate cancer and thyroid cancer, high expressions of HOXA11-AS have been found; furthermore, the upregulated expression of HOXA11-AS were associated with tumor progression and metastasis [12][13][14][17][18][19][20][21][22][23][24][25][26]. Here, we observed overexpression of HOXA11-AS in CRC tissues, and high expression of HOXA11-AS was positively correlated with more aggressive clinicopathological parameters for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, increasing evidences have indicated that LncRNAs play an important role in multiplex tumor biology, 21 for instance gastric cancer, colorectal cancer, and prostate cancer. 22−24 In previous study of OS, Cao K et al 8 have demonstrated that high LncRNA HOXA11-AS has poor survival and is correlated with clinical stage, metastasis. Similarly, the expression of LncRNA XIST promotes OS progression and is associated with clinical features in OS patients, such as metastasis, clinical stage, and tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…7 For example, LncRNA HOXA11-AS is overexpressed and regulates miR-125a-5p/Rab3D in promoting OS metastasis. 8 Lian H et al 9 have declared that Linc00460 could promote cell metastasis via building ceRNA and be functioned as biomarker of prognosis in OS. LncRNA NCRNA00173 is down-regulated and acts as a novel molecular biomarker for HCC.…”
Section: Introductionmentioning
confidence: 99%